Preconcentration of bismuth using nickel hydroxide nanoflower from water samples and determination by FAAS - Yildiz, Baris; Durukan, Ilknur; Saylan, Meltem; Zaman, Buse Tugba; Bakirdere, Sezgin (SPRINGER, 2024)
In this study, a preconcentration strategy based on Ni(OH)(2) nanoflowers (NFs) was developed for the extraction/separation of bismuth ions from environmental water samples before the determination by flame atomic absorption spectrometry (FAAS). The homogeneous coprecipitation method was employed for the synthesis of the flower-shaped Ni(OH)(2) and used as an adsorbent for the preconcentration of bismuth. The extraction variables were determined by a univariate optimization strategy to obtain maximum extraction performance. The optimal parameters of the method were as follows: 15 min mechanical shaking at 120 rpm, pH 6.0 buffer solution (1.0 mL), 20 mg of sorbent, and 250 mu L of 6.0 M nitric acid for the elution. Under the optimized instrumental and extraction conditions, LOD (limit of detection), LOQ (limit of quantitation), and linear dynamic range were determined as 2.8 mu g/L, 9.4 mu g/L, and 0.010-0.30 mg/L, respectively. The enhancement factor of the sorbent-based method was calculated as 139.1-folds by comparing the slopes of calibration plots obtained from FAAS and the preconcentration method. To assess the feasibility and reliability of the developed method, tap water and spring water samples were analyzed under optimized conditions. The satisfactory %recoveries were obtained close to 100% using the direct comparison method. The obtained results show that the presented method is a promising candidate for efficient extraction and trace determination of bismuth in several sample mediums.
Keywords: Ni(OH)(2) nanoflowers; Bismuth; Tap water; Flame atomic absorption spectrometry; Spring water; SOLID-PHASE EXTRACTION; CLOUD POINT EXTRACTION; LIQUID-LIQUID MICROEXTRACTION; ENVIRONMENTAL-SAMPLES; METAL-IONS; LEAD; ADSORPTION; SEPARATION; NANOTUBES; BI(III); Environmental Sciences & Ecology